How multilateral financial institutions promote sustainable water infrastructure planning through economic appraisal: case studies from coastal cities of China. Issue 8 (3rd July 2018) - Wu, Lie; Wang, Zhengzao; Mao, Xianqiang
Abstract : Sustainable urban water infrastructure planning is vital for all cities in developing countries, where rapid urbanization has exacerbated the increasingly burdened environment. Water sustainability is a prerequisite for economic growth, social equity, and living quality in urban areas. This paper documents the current challenges and summarizes the solutions adopted in water infrastructure planning and management. Then, case studies of how multilateral financial institutions have promoted sustainable water infrastructure planning through economic appraisal and the novel approaches adopted for sustainable water infrastructure planning and asset management, are presented for the three cities of Jiaozhou, Cixi, and Fangchenggang. Conclusions are made based on the comparison and analysis of the experiences drawn from the case studies of how economic analysis could help promote sustainable water infrastructure planning and management. It is illustrated that economic analysis that considers ecosystem services supply should be employed more in water infrastructure planning, operation, and management in China.